Plumbagin, a Potent Naphthoquinone from Nepenthes Plants with Growth Inhibiting and Larvicidal Activities - Rahman-Soad, Asifur; Dávila-Lara, Alberto; Paetz, Christian; Mithöfer, Axel (Molecules (Basel, Switzerland), 2021)
Some plant species are less susceptible to herbivore infestation than others. The reason for this is often unknown in detail but is very likely due to an efficient composition of secondary plant metabolites. Strikingly, carnivorous plants of the genus Nepenthes show extremely less herbivory both in the field and in green house. In order to identify the basis for the efficient defense against herbivorous insects in Nepenthes, we performed bioassays using larvae of the generalist lepidopteran herbivore, Spodoptera littoralis. Larvae fed with different tissues from Nepenthes x ventrata grew significantly less when feeding on a diet containing leaf tissue compared with pitcher-trap tissue. As dominating metabolite in Nepenthes tissues, we identified a naphthoquinone, plumbagin (5-hydroxy-2-methyl-1,4-naphthoquinone). When plumbagin was added at different concentrations to the diet of S. littoralis larvae, an EC50 value for larval growth inhibition was determined with 226.5 µg g−1 diet. To further determine the concentration causing higher larval mortality, sweet potato leaf discs were covered with increasing plumbagin concentrations in no-choice-assays; a higher mortality of the larvae was found beyond 60 µg plumbagin per leaf, corresponding to 750 µg g−1. Plant-derived insecticides have long been proposed as alternatives for pest management; plumbagin and derivatives might be such promising environmentally friendly candidates.